1995
DOI: 10.1021/bi00024a002
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Characterization of a Glycosylphosphatidylinositol-Linked Hyaluronidase on Mouse Sperm

Abstract: On the basis of DNA homology to bee venom hyaluronidase, it was recently suggested that the GPI-linked mammalian sperm antigen, PH-20, may function as a cell surface hyaluronidase [Gmachl, M., & Kreil, G. (1993) Proc. Natl. Acad. Sci. U.S.A. 90, 3569-3573]. We have quantified the activity of the soluble acrosomal hyaluronidase of mouse sperm and further demonstrate the existence of a membrane-bound hyaluronidase, detected on both acrosome-intact and acrosome-reacted mouse sperm, distinct from the soluble form … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(64 citation statements)
references
References 28 publications
3
61
0
Order By: Relevance
“…The mice treated with the MBP-mPH20 and rMCMV-mPH20 vaccine formulations that were seropositive on Western blots of BALB/c caudal sperm all recognized a band with apparent molecular mass of , 55 kDa. This is smaller than the principal band of , 67 kDa previously reported by others for mPH20 (SPAM-1), but similar to a minor band present in extracts of acrosome intact caudal sperm (Thaler & Cardullo 1995, Deng et al 1999, Zhang & Martin-DeLeon 2001, Zhang & Martin-DeLeon 2003a. The discrepancy in the estimated sizes of the mPH20 sperm protein may be explained by differences in the SDS-PAGE protocols and molecular mass markers used, although the major band detected in extracts of acrosome-reacted sperm and partially de-glycosylated sperm is reported to be 56 kDa (Deng et al 1999).…”
Section: Discussionsupporting
confidence: 67%
“…The mice treated with the MBP-mPH20 and rMCMV-mPH20 vaccine formulations that were seropositive on Western blots of BALB/c caudal sperm all recognized a band with apparent molecular mass of , 55 kDa. This is smaller than the principal band of , 67 kDa previously reported by others for mPH20 (SPAM-1), but similar to a minor band present in extracts of acrosome intact caudal sperm (Thaler & Cardullo 1995, Deng et al 1999, Zhang & Martin-DeLeon 2001, Zhang & Martin-DeLeon 2003a. The discrepancy in the estimated sizes of the mPH20 sperm protein may be explained by differences in the SDS-PAGE protocols and molecular mass markers used, although the major band detected in extracts of acrosome-reacted sperm and partially de-glycosylated sperm is reported to be 56 kDa (Deng et al 1999).…”
Section: Discussionsupporting
confidence: 67%
“…1). Examples identified through biochemical investigation include GPIanchored proteins (bull: SPAM1 (Morin et al 2010); mouse: PH20 (Thaler & Cardullo 1995) and rat: 2B1 glycoprotein (Seaton et al 2000)), proteins showing carbonyl reductase activity (hamster: P26h (Montfort et al 2002) and pig ), cysteinerich secretory proteins (mouse and rat: CRISP1 (Roberts et al 2006, Busso et al 2007, Da Ros et al 2008) as well as the secreted protein containing N-terminal Notch-like type II EGF repeats and C-terminal discoidin/F5/8 C domains type 1 (SED1 in human and rodents (Ensslin & Shur 2003, Shur et al 2006, Copland et al 2009) and its porcine and bovine homologues, p47 and lactadherin, respectively (Ensslin et al 1998, and in the pig the spermadhesin AQN3, which is secreted in part from the cauda epididymis and mainly from the seminal vesicles . Integral membrane proteins of testicular origin such as proteins of a disintegrin and metalloprotease (ADAM) family have also been described to function in spermoocyte interaction and fertilisation (Evans 2001).…”
Section: Physiological Alterations Of the Sperm Surfacementioning
confidence: 99%
“…It has been demonstrated that GPI-anchored proteins from epididymososmes can be linked to the sperm surface after surface contact and that mouse sperm contain epididymal originated GPI anchored proteins. Examples are CD52 (also called HE5) for human sperm (Yeung et al, 2001;Ermini et al, 2005) and SPAM-1 (also called PH20, P26h,P25b) in a variety of mammalian species (Phelps et al, 1988;Thaler and Cardullo, 1995;Zhang and Martin-Deleon, 2003;Frenette and Sullivan, 2001). It is of interest that we determined the protein carbonyl reductase as one of the zona binding proteins (van Gestel et al, 2005a).…”
Section: Sperm Membrane Microdomains and The Zona Bindingmentioning
confidence: 99%